Um avaliador de cenários simulados para reseqüenciamento da produção em sistemas automatizados de manufatura usando lógica nebulosa - Fernandes, Marcelo Climaites (2004)
In the search for competitive advantages, companies of the manufacture industry segment have been investing in the production flexibility and processes automation, looking for assisting a variety of types of products, following a demand for products and with few manual interventions. In this context, tasks like manufacture integration and production planning and management become more complex. The search for solutions in these tasks should always take into account the desired performance of the productive system, in relation to a series of factors like the attendance of delivery dates. Among the planning tasks, the present proposal is to help the production sequencing. This sequencing can be accomplished in several ways as, for instance, using priority rules. Discrete event systems simulation can be used to test different acceptable sequences of production evaluating the conditions or scenarios. However the simulation typically takes long time, not only to run the models but also for the analysis of the obtained data. To deal with the sequencing task due to situations that happen in moments not determined, the time to analyze or define a new arrangement is a very important factor and needs to be short. This proposal presents a system using fuzzy logic, for the evaluation of data obtained from the simulation of scenarios, considering shop floor conditions, to the production sequencing, in order to take a lower time for the evaluation task.